1993
DOI: 10.2170/jjphysiol.43.697
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intraabdominal Pressure in Venous Blood Drainage from the Prostate into the Vertebral Vein System.

Abstract: We investigated venous blood drainage from the prostate into the vertebral vein system by cineangiography in five mongrel dogs and measured intraabdominal pressure and venous blood pressure in the dog or human to study the role of intraabdominal pressure in the drainage. The averages of intraabdominal pressure and caudal vena caval pressure in the dog were 32.2 +/- 3.0 and 12.8 +/- 1.3 mmHg, respectively, in the supine position, and 39.2 +/- 3.0 and 23.8 +/- 4.0 mmHg, respectively, in the head-up tilt position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The effects of posture on intra-abdominal pressure in humans have been investigated in some clinical cases (Hering et al, 2001;Kiefer et al, 2001;Park, 2000;Suzuki et al, 1993). In a supine position, mean intra-abdominal pressure of mechanically ventilated patients has been estimated as 10-12 mmHg (Hering et al, 2001;Kiefer et al, 2001), although there were great inter-individual variations.…”
Section: Article In Pressmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of posture on intra-abdominal pressure in humans have been investigated in some clinical cases (Hering et al, 2001;Kiefer et al, 2001;Park, 2000;Suzuki et al, 1993). In a supine position, mean intra-abdominal pressure of mechanically ventilated patients has been estimated as 10-12 mmHg (Hering et al, 2001;Kiefer et al, 2001), although there were great inter-individual variations.…”
Section: Article In Pressmentioning
confidence: 99%
“…It therefore seems that as in Subject A, venous blood existing in the intra-abdominal venous system could be conveyed toward veins in the spinal canal by such a small rise in the intra-abdominal pressure. According to observations made by Suzuki et al (1993) in continuous ambulatory peritoneal dialysis patients, voluntary contraction of the abdominal muscles resulted in an increase of intra-abdominal pressure from 8.1 to 50.6 mmHg in a supine position, and from 30.4 to 73.8 mmHg in a standing position. Thus, during exercise, when the abdominal muscles contract in association with body movements and respiration, the intra-abdominal pressure should periodically increase greatly, which may contribute to transferring venous blood returning from the legs to the IVVP.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Campos et al (1985), Goscicka and Spotz (1986), and Wakui et al (1993) reported on the arterial prostate blood supply. Venous vessels between the prostate and vertebral vessels were later described by Japanese scientists (Suzuki et al, 1991(Suzuki et al, , 1992(Suzuki et al, , 1993. A complete description of prostate extraglandular, intraglandular, and zonal blood vessel distribution and their structure and interaction with the glandular parenchyma was made by Stefanov (1998aStefanov ( , 1999a, , and Stefanov et al ( , 2000.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Delivery of these androgens is related to the increase of abdominal pressure (Dhabuwala and Pierrepoint, 1977;Dhabuwala et al, 1978;Pierrepoint et al, 1975). The blood from the prostate venous system passes through v. iliaca interna, v. iliaca communis, and v. cava inferior into the vertebral venous system (Suzuki et al, 1991(Suzuki et al, , 1992(Suzuki et al, , 1993. Although the authors incorrectly used the term v. cava inferior (v. cava caudalis according to NAV, 1983), their conclusions may explain the route of the vertebral metastases of prostate cancer.…”
Section: Principal Prostate Vesselsmentioning
confidence: 99%